STRESSLI VAZIYATLARNING OQIBATLARI (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article examines the effects of stress on the body and mental state. It examines various aspects, including physiological responses to stress, such as increased levels of stress hormones, as well as psychological consequences, such as anxiety, depression and mental imbalance. The long-term effects of stress on the body are also discussed, such as an increased risk of cardiovascular disease, autoimmune disorders and other diseases.